Isogenic genetically-modified and non-genetically-modified corn yields and response to drought and N rates - Bograd, Johazel Hular; Sarobol, Ed; Nakasathien, Sutkhet (Agriculture and Natural Resources, 2022)
Trait integration into conventional hybrids is done via marker-assisted backcrossing on one or both parent lines to achieve near isogenic lines. The parent lines for genetically modified (GM) hybrids were selected based on equivalence in genetics, phenotype and field performance to their conventional counterpart. The response was investigated of two GM variants of a hybrid (herbicide-tolerant Dekalb® 6818R, with transformation event, NK603; herbicide-tolerant and insect-resistant Dekalb® 6818S, with MON89034 × NK603 events “stack”) and its near-isogenic non-GM variant (Dekalb® 6818C) under different water and N conditions. Water, N and their interaction showed significant effects on yield and agrophysiological traits. Combining full irrigation (W3) with 180 kg N/ha maximized the mean (± SD) yield (9,990 ± 318 kg/ha) and biomass (2.04 ± 0.23 kg/m2). Variant as a main effect did not significantly impact yield and agrophysiological traits but isogene interaction with water and N showed a G2 (2.14 ± 0.22 kg/m2) significant advantage over G1 (2.00 ± 0.29 kg/m2) and G0 (2.02 ± 0.30 kg/m2) in accumulating pre-anthesis biomass under W3 across N rates. Under moderate drought (W2) with 0 N, G2 had higher current assimilate transfer to kernels (642.51 ± 83.21 g/m2), percentage contribution of current assimilates to kernel (71.13 ± 2.09 %) and yield (4,950 ± 768 kg/ha) than G1 and G0. Under prolonged drought (W1) with 180 kg N/ha, the G2 yield (7,484 ± 145 kg/ha) was 9% higher than for G1 (6,858 ± 105 kg/ha) and G0 (6,870 ± 208 kg/ha).